Re-inventing ceramic tiles: Using shape grammars as a generative method and the impact on design methodology - Benros, B.; Eloy, S.; Duarte, J. (Proceedings of 16th International Conference CAAD Futures 2015, 2015)
The following paper describes the process and results achieved with the workshop entitled ‘Re-inventing Portuguese ceramic tiles’ reflecting on design methodology and design teaching. Workshop participants were invited to rethink ceramic tile patterns developing a different process which used shape grammars as a generative system. Each participant group developed a three stage task using shape grammars principles and methodology. The preliminary results the work developed are of particular relevance in shape grammar research: firstly shape grammar formulae does not constitute an intuitive process to most creative designers which are often trained to design singular solutions for a specific problem, secondly more than one operative shape grammar can be formulated to represent the same corpus of solutions and lastly the generative potential of grammars transcends the normal capacities of the original grammarist aiding in design exploration and enlarging the corpus of feasible solutions. This paper also reflects on the impact of shape grammars as a design methodology.